Genome-wide identification of short-chain dehydrogenases/reductases genes and functional characterization of ApSDR53C2 in melanin biosynthesis in Arthrinium phaeospermum - Liao, Jiao; Wang, Yisi; Liu, Han; Liu, Sijia; Yan, Peng; Chen, Hang; Li, Shujiang (Frontiers in Microbiology, 2025)
IntroductionArthrinium phaeospermum can cause large areas wilted and death of Bambusa pervariabilis × Dendrocalamopsis grandis, resulting in serious ecological and economic losses. Previous studies found that the appressorium of A. phaeospermum must form to invade the host cells and cause disease. A short-chain dehydrogenase/reductase gene has been shown to maintain the osmotic pressure of the appressorium by synthesizing fungal melanin to penetrate the plant epidermis and cause disease. The SDR gene family of A. phaeospermum was found to be highly expressed during the penetration in the transcriptome sequencing results. Still, the relationship with melanin biosynthesis of A. phaeospermum is not clear.MethodsWe aimed to predict the biological function of the SDR gene family in A. phaeospermum, identify key ApSDR genes with pathogenic roles, and explore the pathogenic mechanism. We have characterized the SDR family of A. pheospermum bioinformatically. Candidate ApSDRs screened by transcriptome sequencing were compared by qPCR experiments to obtain key ApSDRs that may play an important role in infestation and adversity resistance. Knockout mutants, the co-knockout mutant, and backfill mutants of key ApSDRs were obtained for phenotypic and stress conditions analysis. We explored and validated the pathogenic mechanisms through cellulose membrane penetration experiments and analysis of melanin-related gene synthesis levels.Results and discussion180 ApSDRs were identified bioinformatically. After screening six candidate ApSDRs with noticeably elevated expression using transcriptome sequencing, qPCR experiments revealed that ApSDR53C2 and ApSDR548U2 had the highest expression. The results of phenotypic and stress conditions analysis indicate that ApSDRs are critical for the growth, development, stress response, and fungicide resistance of A. phaeospermum. The pathogenicity analysis revealed that ApSDR53C2 and ApSDR548U2 play important roles in virulence, with ApSDR53C2 having a stronger effect. A comparison of melanin synthesis levels between wild-type and ΔApSDR53C2 strains showed that ApSDR53C2 positively regulates melanin biosynthesis to promote penetration. The findings demonstrate that ApSDRs are essential for A. phaeospermum to withstand stress and facilitate melanin biosynthesis, which in turn contributes to its virulence.